Evaluation of Alamar colorimetric broth microdilution susceptibility testing method for staphylococci and enterococci. - Baker, C N (1996)
We compared the results of the Alamar broth microdilution susceptibility testing method with the results of the National Committee for Clinical Laboratory Standards reference broth microdilution method for 119 gram-positive organisms. The strains were tested for their susceptibilities to 20 antimicrobial agents. Only appropriate antimicrobial agents were evaluated for each species of bacteria. Absolute categorical agreement between the reference method and the test method was 91.5% for enterococci, 99.8% for oxacillin-susceptible staphylococci, and 97.4% for oxacillin-resistant staphylococci. Essential agreement (percent complete agreement plus percent minor errors) was > 99% for all organisms tested. The results for enterococci showed no very major errors, one major error with ofloxacin, and numerous minor errors with the quinolones. However, all except one of the minor errors were within +/- 1 log2 dilution of the reference result. For staphylococci, only 2 very major errors (one each with chloramphenicol and oxacillin), 1 major error (chloramphenicol), and 15 minor errors (multiple drugs) were observed. The Alamar colorimetric system was easy to use and the results were easy to read. It appears to be an acceptable method for antimicrobial susceptibility testing of staphylococci and enterococci.